Pembatalan Desain Industri karena Tidak Adanya Unsur Kebaruan dalam Putusan Pengadilan Negeri Jakarta Pusat Nomor 78/Pdt.Sus-Hak Kekayaan Intelektual/Desain Industri/2022/Pn Niaga Jkt.Pst - Yoan Sally E Br Ginting; OK. Saidin; Leviza Jelly (Jurnal Hukum Lex Generalis, 2025)
This research is motivated by the increasing number of industrial design registrations that do not meet the novelty requirement, potentially harming original design owners and causing legal disputes. The case analyzed is the Commercial Court Decision at the Central Jakarta District Court Number 78/Pdt.SusHKl/lndustrial Design/2022/PN Niaga Jkt.Pst, which annulled the registration of a suitcase generator industrial design because it had been previously published abroad and exceeded the six-month grace period. The study is descriptive-analytical in nature, using secondary data sources consisting of primary; secondary, and tertiary legal materials. In conclusion, the cancellation of industrial design registrations that do not meet the novelty requirement is legally appropriate and necessary.